The Influence of Muqātil ibn Sulaymān in the Development of Qur’anic Exegetical Methodology: Cross-Referential and Narrative-Based Approaches - Kusmana Kusmana (Universitas Islam Negeri Imam Bonjol Padang, 2026)
The aim of this article is to formulate the contributions of Muqātil bin Sulayman (d. 767), a Muslim scholar from Merv, Central Asia, in the formulation of classical Quranic interpretation and its later development, particularly his idea about Cross-referential interpretation, which seeks meaning by connecting terms across different Qur'anic verses, and Narrative-based interpretation, which considers multiple sources to provide context for the verses being explained. Using a descriptive-analytical method, the study examines how these two approaches shaped classical tafsir and its development. The study finds that the first idea became a foundation for orthodox tafsir i.e., bi al-Ma'thur, while the second one contributed to early contextual tafsir, though it faced criticism regarding the validity of its sources. Additionally, despite criticisms of foundationalism, cross-referential interpretation became an epistemological basis for the development of modern tafsir methods, such as it is largely used in thematic tafsir (tafsir maudhui) and tafsir maqasidi (objective-based interpretation), due to their comprehensive and cohesive approach to Qur'anic interpretation.